2015
DOI: 10.1002/ptr.5434
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil‐derived Oleocanthal as Potent Inhibitor of Mammalian Target of Rapamycin: Biological Evaluation and Molecular Modeling Studies

Abstract: The established anticancer and neuroprotective properties of oleocanthal combined with the reported role of mammalian target of rapamycin (mTOR) in cancer and Alzheimer’s disease development encouraged us to examine the possibility that oleocanthal inhibits mTOR. To validate this hypothesis, we docked oleocanthal into the adenosine triphosphate binding pocket of a close mTOR protein homologue, namely, PI3K-γ. Apparently, oleocanthal shared nine out of ten critical binding interactions with a potent dual PIK3-γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 46 publications
1
71
0
Order By: Relevance
“…Earlier studies indicated that (−)-oleocanthal is a potential inhibitor of the hepatocyte growth factor receptor (c-Met) pathway in breast cancer cells (Akl et al, 2014; Elnagar et al, 2011; Mohyeldin et al, 2016b). The antiproliferative effects of (−)-oleocanthal are mediated by inhibiting multiple c-Met downstream signaling molecules including protein kinase B (Akt), mitogen-activated protein kinase (MAPK), signal transducers and activators of transcription-3 (STAT-3), and mammalian target of rapamycin (mTOR) in multiple cancer cells (Akl et al, 2014; Fogli et al, 2016; Khanal et al, 2011; Khanfar et al, 2015; Pei et al, 2016; Scotece et al, 2013). In addition, (−)-oleocanthal induced cancer cell arrest by modulating the expression of cyclins, cyclin-dependent kinases, and arrest proteins (Akl et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies indicated that (−)-oleocanthal is a potential inhibitor of the hepatocyte growth factor receptor (c-Met) pathway in breast cancer cells (Akl et al, 2014; Elnagar et al, 2011; Mohyeldin et al, 2016b). The antiproliferative effects of (−)-oleocanthal are mediated by inhibiting multiple c-Met downstream signaling molecules including protein kinase B (Akt), mitogen-activated protein kinase (MAPK), signal transducers and activators of transcription-3 (STAT-3), and mammalian target of rapamycin (mTOR) in multiple cancer cells (Akl et al, 2014; Fogli et al, 2016; Khanal et al, 2011; Khanfar et al, 2015; Pei et al, 2016; Scotece et al, 2013). In addition, (−)-oleocanthal induced cancer cell arrest by modulating the expression of cyclins, cyclin-dependent kinases, and arrest proteins (Akl et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the role of secoiridoids derived from Olea europaea L. has been investigated in different types of cancerous processes (Tables 1 and 2). OLE showed strong antiproliferative and downregulated the expression of phosphorylated mTOR [112] BT-474 [0-100 µ g/mL] OLE reduced breast cancer progression and locoregional recurrence models [113] MDA-MB-231 5 mg/mL OLE was able to control breast cancer progression [114] BT OLE showed strong antiproliferative and downregulated the expression of phosphorylated mTOR [112] BT-474 [0-100 µ g/mL] OLE reduced breast cancer progression and locoregional recurrence models [113] MDA-MB-231 5 mg/mL OLE was able to control breast cancer progression [114] BT OLE showed strong anti-proliferative and down-regulated the expression of phosphorylated mTOR [112] BT-474 [0-100 µg/mL] OLE reduced breast cancer progression and locoregional recurrence models [113] MDA-MB-231 5 mg/mL OLE was able to control breast cancer progression [114] BT-474 and MDA-MB-231…”
Section: Olive Tree Secoiridoids and Cancermentioning
confidence: 99%
“…The prevention of tumor recurrence was associated with the down-regulation of MET and HER 2 receptors and suppression of receptor activation [129]. OLE showed a strong anti-proliferative role against several breast cancer cell lines; for example, OLE was able to down-regulate the expression of phosphorylated mammalian target of rapamycin (mTOR) in metastatic MDA-BD-231 breast cancer cell lines [112] and inhibit the proliferation, migration, and invasion of the epithelial human breast cancer and prostate cancer cell lines (MCF7; MDA-BD-231; and PC3). In addition, LeGendre et al demonstrated that OLE selectively and rapidly induces cell death in cancer cells without being cytotoxic to noncancerous cells.…”
Section: Ol-aglyconementioning
confidence: 99%
“…Heat shock proteins though can interact with OC, so they are possible targets for cancer treatment [74]. Another way that OC can be used, as antitumor agent, is through targeting and downregulating mTOR, a protein that was found to participate in cancer, and especially to breast cancer, with the IC50 of OC to be in the range of nM [75].…”
Section: Oleocanthalmentioning
confidence: 99%